Antimicrobial activity of the novel bacteriocin AP7121: from in vitro assays to an in vivo preliminary intranasal treatment approach - Schofs, Laureano (2023)
The impact of staphylococci infections on human and animal health increased as result of its ability to become resistant to antimicrobials. Most Staphylococcus spp. (Staph) infections are endogenously acquired, and treatment of nasal carriage is one strategy for prevention. AP7121 bacteriocin, showed in vitro bactericidal activity against Staph. The main goals of this study were: a) to assess the nasal carriage of Staphylococcus species in asymptomatic dogs, and b) to test the effect of intranasal administration of AP7121 in the staphylococci population. Dogs were randomly allocated in two groups (n=3) and two intranasal administration protocols were evaluated as follows: protocol A: canines received one dose of either 150 µL of sterile saline solution (SSS) (control group) or 150 µL of AP7121 solution (330 µg/mL) (AP7121 group); protocol B: dogs received 100 µL every 24 h for 3 days of SSS or AP7121 (330 µg/mL). Previous to each treatment (T0) and 24 h after the topical treatment (T1), standardized nasal swabs samples of both nasal vestibules were taken. Swabs were systematically inoculated and cultured in Mannitol salt agar and Blood agar. Staph isolates were phenotypically characterized according to antimicrobial sensibility using the disk diffusion method and VITEK® 2 system. Fischer exact Test was used for statistical analysis of treatments. Variability in Staphylococcus species was found in many cases among individual dogs in T0 and T1. Fifty Staph strains were isolated, being 58% (29/50) resistant to Penicillin and 4% (2/50) showing inducible macrolide and lincosamide resistance. Protocol A treatment failed to reduce the viability of the nasal staphylococci population. However, protocol B (3 doses of AP7121) showed a significant 50% of decolonization (p<0.01). In conclusion, the antimicrobial effect of AP7121 against Staph could be explored as a potential alternative for nasal decolonization therapy in dogs, as in previous clinical humans´ studies.